PENERAPAN METODE PLACEMAKING DALAM REDESAIN PASAR BARANG BEKAS DI TAMAN PURING, JAKARTA SELATAN - Samosir, Yustina Regitha; Choandi, Mieke (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
As time passed, Puring Park Market lost its identity as a place to sell used goods, reinforcing Edward Relph's (1976) theory of a Placeless Place, a phenomenon in which meaningful and unique places were replaced by monotonous and meaningless environments, due to a lack of sensitivity to the significance of places. The objective of this plan is to counteract the exploitation of public space that is not functioning optimally, to build a strong local identity by making it a bridge or space between individuals or communities in the Puring Park Market through proposed new programs such as commercial, creative Space, and communal areas. This research is qualitative. Data collection methods through the phase of interviews, site, and area observations, and then documentation. They also perform location analysis to obtain historical data, user, activity, and issues and problems on the location. The location of the research conducted at Puring Park Market, New Kebayoran - South Jakarta, aims to find out the role of architecture in restoring the identity of the Puring Garden Market. This design is adapted from the concept of modular design with the use of space in an adaptive time context, as well as elements of architecture undergoing changes or interactions of activity at different times. Create a comfortable public space with an attractive and unique impression with the processing of streetscape as an outdoor market. With the presence of a new identity at the Puring Park Market, it is expected to provide jobs to boost the local economy. Keywords: architecture; identity; Taman Puring Market; placeless place Abstrak Pasar Taman Puring dahulunya merupakan tempat berjualan barang-barang bekas. Seiring berjalannya waktu, Pasar Taman Puring kehilangan identitasnya sebagai tempat berjualan barang bekas, semakin memperkuat  teori Edward Relph (1976) tentang Placeless Place yang merupakan fenomena di mana tempat-tempat yang bermakna serta unik digantikan oleh lingkungan monoton dan tidak bermakna, ini disebabkan oleh kurangnya kepekaan terhadap signifikansi tempat. Tujuan Perancangan ini untuk menanggulangi pemanfaatan ruang publik yang tidak berfungsi secara optimal, untuk membangun identitas lokal yang kuat dengan menjadikannya jembatan atau ruang antar individu atau kelompok masyarakat di Pasar Taman Puring melalui program baru yang diusulkan seperti commercial, creative Space, dan  communal area. Penelitian ini bersifat kualitatif. Metode pengumpulan data melalui tahap wawancara, observasi tapak dan kawasan lalu dokumentasi. Lalu juga melakukan analisis lokasi dalam memperoleh data sejarah, pengguna, aktivitas, serta isu dan masalah pada lokasi. Lokasi penelitian dilakukan di Pasar Taman Puring, Jakarta Selatan, bertujuan untuk mengetahui Bagaimana peran arsitektur dalam mengembalikan identitas Pasar Taman Puring. Perancangan ini diadaptasi dari konsep desain modular dengan penggunaan ruang dalam konteks waktu yang adaptive, serta elemen-elemen arsitektur mengalami perubahan atau interaksi aktivitas pada waktu berbeda. Menciptakan ruang publik yang nyaman dengan kesan yang menarik dan unik dengan pengolahan streetscape sebagai outdoor market. Dengan hadirnya identitas baru pada Pasar Taman Puring diharapkan dapat memberikan lapangan pekerjaan meningkatkan perekonomian masyarakat setempat.